2014
DOI: 10.3109/09593985.2014.982774
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the use of a dual-channel functional electrical stimulation system on gait, balance and balance confidence of an adult with spastic diplegic cerebral palsy

Abstract: The purpose of this case report is to determine the effects of a dual-channel functional electrical stimulation (FES) system on gait and balance of a 57-year-old male diagnosed with spastic diplegic cerebral palsy (CP). Outcome measures included the: Activities-specific Balance Confidence Scale (ABC); Dynamic Gait Index (DGI); Observational Gait Scale (OGS) and Tinetti Performance Oriented Mobility Assessment (POMA). Assessments were completed with and without use of FES during the initial examination and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Eleven studies reported NMES-assisted gait for strengthening and improving gait pattern, including one case report ( Robinson et al, 2015 ), three single-subject research design studies (SSRD) ( Chan et al, 2004 ; Pool et al, 2014 ; Gonçalves et al, 2019 ), three prospective trials ( Johnston et al, 2004 ; Prosser et al, 2012 ; Damiano et al, 2013 ), and four RCTs ( Pool et al, 2016 ; 2015 , van der Linden et al, 2003 , 2008 ). Various NMES devices were used, including surface electrodes for non-wearable units targeting the gluteals, quadriceps, gastrocnemius, and tibialis anterior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies reported NMES-assisted gait for strengthening and improving gait pattern, including one case report ( Robinson et al, 2015 ), three single-subject research design studies (SSRD) ( Chan et al, 2004 ; Pool et al, 2014 ; Gonçalves et al, 2019 ), three prospective trials ( Johnston et al, 2004 ; Prosser et al, 2012 ; Damiano et al, 2013 ), and four RCTs ( Pool et al, 2016 ; 2015 , van der Linden et al, 2003 , 2008 ). Various NMES devices were used, including surface electrodes for non-wearable units targeting the gluteals, quadriceps, gastrocnemius, and tibialis anterior.…”
Section: Resultsmentioning
confidence: 99%
“…The eleven studies that investigated NMES-assisted gait found improved muscle structure, strength, SMC, gross motor skills, and gait ( van der Linden et al, 2003 , 2008 ; Chan et al, 2004 ; Johnston et al, 2004 ; Prosser et al, 2012 ; Damiano et al, 2013 ; Pool et al, 2016 , 2015 , 2014 ; Robinson et al, 2015 ; Gonçalves et al, 2019 ). NMES-assisted gait resulted in increased muscle volume of tibialis anterior as assessed on MRIs ( Pool et al, 2016 ), increased tibialis anterior CSA as assessed on ultrasound ( Damiano et al, 2013 ), increased strength as assessed by dynamometers ( Pool et al, 2016 , 2014 ), improved SMC as assessed by SCALE ( Pool et al, 2016 ), improved gross motor skills as assessed by GMFM ( van der Linden et al, 2003 ; Chan et al, 2004 ; Johnston et al, 2004 ; Gonçalves et al, 2019 ), and improved gait as assessed by kinematics, kinetics, and temporal-spatial parameters ( Chan et al, 2004 ; Johnston et al, 2004 ; van der Linden et al, 2008 ; Prosser et al, 2012 ; Pool et al, 2015 ; Robinson et al, 2015 ). Compliance was reported to be high for NMES intervention ( Chan et al, 2004 ; Prosser et al, 2012 ; Pool et al, 2016 , 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…This early hypothesis is supported by the case studies published in Rose et al (21) and Behboodi et al (20). Additionally, a single subject case study published in 2015, assessing the effects of gait-specific multi-channel stimulation to the tibialis anterior and hamstrings in an adult with CP, demonstrated improvements in the Dynamic Gait Index, Performance Oriented Mobility Assessment, Observational Gait Scale, and Activities-specific Balance Confidence Scale scores (42). However, these are all case study examples, and the benefits of a multi-channel NMES system must be born out in a larger study.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Six Minute Walk Test (6MWT) used in Phase I: examines physical functioning capacity by assessing walking distance over a total of six minutes on a hard, flat surface. 31 Test-retest reliability as ICC = 0.88 -0.91 overtime in heart failure patients.…”
Section: Physical Functioningmentioning
confidence: 99%